Exhaled breath condensate (EBC) for SARS-CoV-2 diagnosis still an open debate. (1st April 2022) - Loconsole, Daniela; Paola, Pierucci; Daniele, Casulli; Federica, Barratta; Maria, Chironna; Giovanna Elisiana, Carpagnano
Abstract: The real-time PCR (RT-PCR) on nasopharyngeal swabs (NPS) is the gold standard for the diagnosis of SARS-CoV-2. The exhaled breath condensate (EBC) is used to perform collection of biological fluid condensed in a refrigerated device from deep airways' exhaled air. We aimed to verify the presence of SARS-CoV-2 virus in the EBC from patients with confirmed SARS-CoV-2 infection by RT-PCR, and to determine if the EBC may represent a valid alternative to the NPS. Seventeen consecutive patients admitted to the Emergency Department of the Policlinico were enrolled in the present study with RT-PCR, clinical and radiological evidence of SARS-CoV-2. Within 24 h from the NPS collection the EBC collection was performed on SARS-CoV-2 positive patients. Informed written consent was gathered and the Ethic Committee approved the study. The mean age of patients was 60 years (24–92) and 64.7% (11/17) were male. Patient n.9 and n.17 died. All NPS resulted positive for SARS-CoV-2 at RT-PCR. RT-PCR on EBC resulted negative for all but one patients (patient n.12). In this study we did not find any correlation between positive NPS and the EBC in all but one patients enrolled. Based on these data which greatly differ from previous reports on the topic, this study opens several questions related to small differences in the complex process of EBC collection and how EBC could be really standardized for the diagnosis of SARS-CoV-2 infection. Further studies will be warranted to deepen this topic.